Plastic ingestion risk is related to the anthropogenic activity and breeding stage in an Antarctic top predator seabird species - Ibañez, Andres Esteban; Morales, Lara Mariel; Torres, Diego Sebastian; Borghello, Paloma; Haidr, Nadia Soledad; Montalti, Diego (Marine Pollution Bulletin)
During the last decades plastic pollution has become a common issue in marine environments. Studies on seabirds have focused on species that ingest plastics mistaken for prey or indirectly through their preferred prey or, on how foraging strategy influences this behaviour. We evaluated plastic ingestion in relation to the proximity of nests to areas with different anthropogenic pressure, breeding status and breeding stage. We analyzed regurgitated pellets (n = 1001) from a seabird, the Brown Skua (Stercorarius antarcticus lonnbergi) at Esperanza/Hope Bay, Antarctic Peninsula. Plastics were found in 9% of pellets, only in breeders from an area with high antropogenic activity. The prevalence of plastic increased during the brooding of chicks stage, when skuas expand their feeding niche. Our results support previous work which demonstrated that seabirds with wider feeding niche show higher loads of plastics. Altogether, this provides insights into the dynamics of plastic transfer within the environment. Fil: Ibañez, Andres Esteban. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Morales, Lara Mariel. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina Fil: Torres, Diego Sebastian. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina Fil: Borghello, Paloma. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina Fil: Haidr, Nadia Soledad. Fundación Miguel Lillo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico - Tucumán. Unidad Ejecutora Lillo; Argentina Fil: Montalti, Diego. Universidad ...